2004
DOI: 10.2739/kurumemedj.51.185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Milnacipran on the Inhibitory Postsynaptic Potential in Neurons of the Rat Locus Coeruleus

Abstract: Effects of milnacipran (MIL), a serotonin and noradrenaline reuptake inhibitor (SNRI), on synaptic transmission were examined in the rat locus coeruleus (LC). Bath-application of MIL produced a hyperpolarization associated with a decrease in input resistance of LC neurons. The MIL-induced hyperpolarization reversed polarity near the equilibrium potential of K+. The MIL-induced hyperpolarization was blocked by yohimbine (1 microM). Clonidine, but not serotonin (5-hydroxytryptamine; 5-HT), produced a hyperpolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Similar studies on the noradrenergic system found that milnacipran hyperpolarizes locus coeruleus neurons and enhances the inhibitory postsynaptic potential by increasing endogenous NE at synapses within locus coeruleus (Kuwahata et al 2004). …”
Section: Basic Studiesmentioning
confidence: 85%
“…Similar studies on the noradrenergic system found that milnacipran hyperpolarizes locus coeruleus neurons and enhances the inhibitory postsynaptic potential by increasing endogenous NE at synapses within locus coeruleus (Kuwahata et al 2004). …”
Section: Basic Studiesmentioning
confidence: 85%